AB0412 Preclinical PK and Safety Assessment of the Proposed Adalimumab Biosimilar Gp2017, Compared to Humira®. (10th June 2014) - Kronthaler, U.; Baron, M.; Poetzl, J.; Da Silva, A.
Abstract : Background: TNFα inhibitors are highly effective drugs for the treatment of inflammatory disorders such as rheumatoid arthritis. Biosimilars are approved biologics with comparable quality, safety and efficacy to a reference product, which has lost exclusivity, aiming to offer more affordable treatment to patients. Objectives: Here we present results on the pre-clinical in-vivo characterization of the proposed adalimumab biosimilar GP2017 in terms of pharmacokinetics as well as safety. Methods: Pharmacokinetic characteristics (AUC, Cmax ) of GP2017 and Humira® (AbbVie Ltd.) following s.c. administration were compared in two settings: 1) a single administration of 10 mg/kg in NZW rabbits (n=20 male/group; housed individually) with no binding of adalimumab to endogenous TNFα; 2) multiple administrations of 100 mg/kg each in cynomolgus monkeys (n=5-6/group; female & male; social housing) as part of a placebo controlled toxicity study. Primates were selected as adalimumab binds to their endogenous TNFα. For both settings, injection volumes per site were chosen to match clinical practice, i.e. approx. 0.8 mL/site. Serum concentration was determined for 5 (monkeys) or up to 11 weeks (rabbits), using validated ELISAs. For assessment of safety in the toxicity study, all organ systems were monitored. In addition, a cross-reactivity study on a broad set of human tissues was conducted to exclude unexpected off-target binding. Results: Single s.c. administration in rabbits resulted in a similar mean AUC0–168h and Cmax, at a low Coefficient of Variation (CV) for both products: Terminal half-life was also similar at 227 (Humira®) and 203 hours (GP2017). In monkeys AUC and Cmax were similar, as well. Specifically, AUC0–96h ratio for the first injection was 82% for male and 110% for female animals (mean 96%). At the second injection, the ratio was 89% and 112%, respectively (mean 101%). The Cmax ratio was 96% and 101% at the first and second injection. The accumulation of Cmax and AUC0–96h was 2-fold upon the second and up to 4-fold upon fifth and last injection. Both products showed the same behavior in this respect. Safety assessment demonstrated lack of treatment-related adverse changes in e.g. clinical signs, body weight, blood pressure, hematology, clinical chemistry and histopathology. Finally, no unexpected off-target binding was observed with GP2017 in the human tissues cross-reactivity study, thus suggesting a low risk of unexpected safety signals. Conclusions: Pre-clinical pharmacokinetic studies are a sensitive means to characterize proposed biosimilars compared to their reference product. Similar AUC and Cmax of GP2017 and Humira® are shown here in two species, upon single or repeated s.c. administration. At a dose level substantially exceeding clinical practice, the proposed biosimilar to adalimumab GP2017 was as well tolerated as Humira®, with no adverse effects, supporting start of clinical development phase. Ongoing clinical trial(s) will help provide confirmation of similar pharmacokinetics, efficacy and safety of GP2017 in humans compared to Humira®. Disclosure of Interest: U. Kronthaler Employee of: Hexal AG, M. Baron Employee of: Hexal AG, J. Poetzl Employee of: Hexal AG, A. da Silva Employee of: Hexal AG DOI: 10.1136/annrheumdis-2014-eular.1545